Dominance of Particulate Mercury in Stream Transport and Rapid Watershed Recovery from Wildfires in Northern California, USA - Ku, Peijia; Tsui, Martin Tsz-Ki; Uzun, Habibullah; Chen, Huan; Dahlgren, Randy A.; Hoang, Tham C.; Karanfil, Tanju; Zhong, Huan; Miao, Ai-Jun; Pan, Ke; Coleman, James S.; Chow, Alex Tat-Shing (American Chemical Society (ACS), 2024)
Frequency and intensity of wildfires are expected to increase due to climate change, especially in areas with a long summer drought. Forests are a major sink for the global pollutant mercury (Hg), and fluvial transport of Hg from recently burned watersheds has not been widely investigated. Here, we examined two years of fluvial transport of Hg and its speciation (total Hg, methyl-Hg, particulate, and dissolved forms) under storm events and baseflow in two recently burned watersheds with different burned proportions and one nonburned reference watershed in the Coastal Ranges of northern California. We examined postfire storm-event transport of Hg and its methylated form (methyl-Hg), addressed the importance of the "initial runoff pulse" to postfire Hg fluvial transport and its predominant association with suspended solids, and elucidated potential sources of Hg exports from the burned landscapes using geochemical indicators, which suggested that ash materials were likely the significant sources of particulates in the first high-flow season postfire but not subsequently. The maximum total suspended solid and total Hg levels in the "first pulse" at the severely burned watershed were 442 and 46 times higher, respectively, than those at the reference watershed. Stream suspended solid and Hg levels declined substantially in the burned watersheds after just a few months of rainfall likely due to the rapid regrowth of vegetation commonly observed in postfire landscapes, implying that the wildfire effects on immediate Hg inputs from the burned landscape are at most transient in nature.
Keywords: mercury; Rivers; Climate Change; methylmercury; Mercury; rainstorms; fluvial transport; wildfire; California; Water Pollutants, Chemical; Wildfires; Environmental Monitoring